Effect of atenolol pre-treatment in heart damage in a model of intestinal ischemia-reperfusion - Okada, Mieko; Falcão, Luiz Fernando Reis; Ferez, David; Martins, José Luiz; Errante, Paolo Ruggero; Rodrigues, Francisco Sandro Menezes; Caricati-Neto, Afonso; Marinho, Márcia [UNESP]; Fenelon, Guilherme; Souza Oliveira-Júnior, Itamar (FapUNIFESP (SciELO), 2017)
Purpose: To investigate the effects of atenolol in inflammatory mediator and oxidative stress in a myocardial injury by intestinal ischemia/reperfusion in rat model. Methods: Adult Wistar male rats were randomly (n=8), anesthetized and divided in: Sham: submitted to operation only; group SS+IR: intravenous saline infusion following superior mesenteric artery occlusion during 60 minutes (ischemia) and open for 120 minutes (reperfusion); group AT+IR: intravenous atenolol infusion (2 mg/kg) following superior mesenteric artery occlusion during 60 minutes (ischemia) and open for 120 minutes (reperfusion); and group AT+I+AT+R: intravenous atenolol infusion following superior mesenteric artery occlusion during 60 minutes (ischemia) and in the time 45 minutes other atenolol doses were administrated and the artery was open for 120 minutes (reperfusion), all animals were submitted to muscular relaxation for mechanical ventilation. In the end of experiment the animals were euthanized and the hearts tissue were morphology analyzed by histology and malondialdehyde by ELISA, and the plasma were analyzed for tumor necrosis factor-alpha by ELISA. Results: The group SS+IR demonstrated the higher malondialdehyde levels when compared with the atenolol treated-groups (p=0.001) in the heart tissue. The tumor necrosis factoralpha level in plasma decrease in the treated groups when compared with SS+IR group (p=0.001). Histology analyses demonstrate pyknosis, edema, cellular vacuolization, presence of inflammatory infiltrate and band contraction in the heart tissue of the rats. Conclusion: Atenolol significantly reduce the degree of cardiac damage after intestinal ischemia-reperfusion.
Keywords: Adrenergic antagonists; Atenolol; Cytokines; Ischemia; Oxidative stress; Rats; Reperfusion